2014
DOI: 10.1590/s1980-57642014dn83000006
|View full text |Cite
|
Sign up to set email alerts
|

Automatic classification of written descriptions by healthy adults: An overview of the application of natural language processing and machine learning techniques to clinical discourse analysis

Abstract: Discourse production is an important aspect in the evaluation of brain-injured individuals. We believe that studies comparing the performance of brain-injured subjects with that of healthy controls must use groups with compatible education. A pioneering application of machine learning methods using Brazilian Portuguese for clinical purposes is described, highlighting education as an important variable in the Brazilian scenario.ObjectiveThe aims were to describe how to:(i) develop machine learning classifiers u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“… Toledo et al (2014) added an automated component to these analyses. They used a simple (“The Tripping Woman Picture”) and a complex line drawing (“The Traffic Chaos Picture”) that were also used by Forbes-McKay et al (2013 , 2014) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Toledo et al (2014) added an automated component to these analyses. They used a simple (“The Tripping Woman Picture”) and a complex line drawing (“The Traffic Chaos Picture”) that were also used by Forbes-McKay et al (2013 , 2014) .…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that, for data classification, a specific type of machine learning (i.e., Support Vector Machine with a radial basis function kernel) performed best. Moreover, correlation-based feature selection was the preferred method to replace manual selection with ( Toledo et al, 2014 ). These findings also support the idea that groups can be distinguished on the basis of specific linguistic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Coh-Metrix-Dementia is based on a previous tool for discourse analysis, named Coh-Metrix-Port (SCARTON; ALUíSIO, 2010), which was already used in a clinical discourse analysis study to classify written descriptions of healthy adults (TOLEDO et al, 2014). Based on previous studies using metrics and machine learning classifiers for the English language in clinical settings (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Foi desenvolvido no NILC e adiciona novas métricas as 48 existentes no Coh-Metrix-Port. As novas métricas do Cohmetrix-Dementia incluem a análise de semântica latente, medidas de diversidade lexical, complexidade sintática e densidade semântica (Toledo et al, 2014;Cunha, 2015). Essa ferramenta mostrou a possibilidade de diferenciação entre indivíduos cognitivamente sadios, com comprometimento cognitivo leve e com doença de Alzheimer, com base na análise computadorizada das amostras de discurso da história da Cinderela.…”
Section: Análise Computadorizada E Discursounclassified
“…Neste sentido, nos últimos anos, tem surgido crescente número de pesquisas relacionadas ao processamento automatizado de dados de discurso. Esses estudos têm demonstrado a possibilidade de realizar diagnóstico diferencial e verificar a evolução de doença por meio de análises utilizando tecnologia computadorizada (MacWhinney, 2000;Fergadiotis et al, 2013;Fraser et al, 2014;Toledo et. al, 2014;Cunha, 2015).…”
Section: Introdução E Justificativaunclassified